Prevalence of antibodies against measles, mumps, and rubella before and after vaccination of school-age children with three different triple combined viral vaccines, Rio Grande do Sul, Brazil, 1996 - Santos, Boaventura Antonio dos (2013)
Objective. We evaluated the seroprevalence for measles, mumps, and rubella in school-age children (6–12 years old) before and after the administration of three triple combined viral vaccines. Methods. In two municipal schools of Rio Grande do Sul, Brazil, 692 blood samples were collected before vaccination and 636 samples 21 to 30 days after vaccination during 1996. IgG antibody seropositivity was investigated by enzyme-linked immunosorbent assay (measles and mumps with Enzygnost [Behring, Marburg, Germany]; rubella with Rubenostika [Organon Teknica, Boxtel, the Netherlands]). The vaccines compared were: A: E-Zagreb, L-Zagreb, and Wistar RA 27/3 (Tresivac); B: Moraten, J-Lynn, and Wistar RA 27/3 (M-M-R II); and C: Schwarz, Urabe AM-9, and Wistar RA 27/3 (Trimovax). Results. Before vaccination, 79.2% [95% confidence interval (CI) = 76.0%–82.2%] of the samples were positive for measles, 69.4% (95% CI = 65.8%–72.8%) for mumps, and 55.4% (95% CI = 51.6%–59.2%) for rubella. After vaccination with the A, B, and C vaccines, seropositivity was 100.0%, 99.5%, and 100.0%, respectively for measles; 99.5%, 94.5%, and 92.0% for mumps; and 92.6%, 91.3%, and 88.6% for rubella. Conclusions. About one-fifth (20.8%) of the schoolchildren who could have been vaccinated against measles at age 9 months had levels of antibodies insufficient for protection. In the sample of schoolchildren without previous vaccination against mumps and rubella, high proportions of susceptible levels were found. All vaccines were immunogenic, but vaccine A yielded a seroconversion rate of 99.5% for the mumps component, which was significantly higher than the other two vaccines (P < 0.01).